PENGARUH MODAL KERJA DAN LEVERAGE TERHADAP PROFITABILITAS : Studi pada Perusahaan Sub Sektor Kosmetik dan Keperluan Rumah Tangga Periode 2007-2013 - Nababan, Debora Uli Tua (2014)
This study examines the phenomenon of declining profitability in There are several factors that can affect the lower level of profitability, one of which is working capital and leverage at Cosmetics and Households Goods company characterized by inefficient. This study aimed to obtain a working capital of Cosmetics and Households Goods company, obtain leverage Cosmetics and Households Goods company, obtain a profitability on Cosmetics and Households Goods company, obtain a working capital and leverage level of influence on the profitability of the Cosmetics and Households Goods company. Objects in this study are the financial statements. Cosmetics and Households Goods company period 2007-2013. Type of research is descriptive and verification, the method used in this study is a quantitative, . The analysis in this research used linear regression by SPSS 21.0 as a tool. Based on the results of this researchs can be knows, working capital at Cosmetics and Households Goods company period 2007-2013 decreased, then leverage at Cosmetics and Households Goods company period 2007-2013 there are some companies that have high debt so causes higher average, profitability at Cosmetics and Households Goods company period 2007-2013 experienced a significant decline. Based on research show that the working capital and leverage affect profitability. Based on the obtained results the author recommends the authors suggest that companies pay attention to the use of working capital effectively and efficiently in order to increase company profit that affect both the profitability and company should be careful and more selective in the use of debt so that debt can't generate profit result in the losses.